Smart Wound Scaffolds: Light‐Controlled Growth Factors Release on Tetrapodal ZnO‐Incorporated 3D‐Printed Hydrogels for Developing Smart Wound Scaffold (Adv. Funct. Mater. 22/2021). (26th May 2021) - Siebert, Leonard; Luna‐Cerón, Eder; García‐Rivera, Luis Enrique; Oh, Junsung; Jang, JunHwee; Rosas‐Gómez, Diego A.; Pérez‐Gómez, Mitzi D.; Maschkowitz, Gregor; Fickenscher, Helmut; Oceguera‐Cuevas, Daniela; Holguín‐León, Carmen G.; Byambaa, Batzaya; et al.
Abstract : In article number 2007555, Leonard Siebert, Eunjung Lee, Su Ryon Shin, and co‐workers develop a 3D printed smart wound scaffold encapsulating growth factors decorated with light‐sensitive and antibacterial tetrapodal zinc oxide (t‐ZnO) microparticles for the treatment of chronic wounds. The multifunctional pro perties of the smart scaffold combined with light‐triggered angiogenic factor release, antibacterial properties, and tissue compatibility enable fast wound recovery.